Comparison of implant placement accuracy in two different preoperative digital workflows: navigated vs. pilot-drill-guided surgery - Johannes Spille; Feilu Jin; Eleonore Behrens; Yahya Açil; Jürgen Lichtenstein; Hendrik Naujokat; Aydin Gülses; Christian Flörke; Jörg Wiltfang (SpringerOpen, 2021)
Abstract Background The aim of the study is to evaluate the accuracy of a new implant navigation system on two different digital workflows. Methods A total of 18 phantom jaws consisting of hard and non-warping plastic and resembling edentulous jaws were used to stimulate a clinical circumstance. A conventional pilot-drill guide was conducted by a technician, and a master model was set by using this laboratory-produced guide. After cone beam computed tomography (CBCT) and 3D scanning of the master models, two different digital workflows (marker tray in CBCT and 3D-printed tray) were performed based on the Digital Imaging Communication in Medicine files and standard tessellation language files. Eight Straumann implants (4.1 mm × 10 mm) were placed in each model, six models for each group, resulting in 144 implant placements in total. Postoperative CBCT were taken, and deviations at the entry point and apex as well as angular deviations were measured compared to the master model. Results The mean total deviations at the implant entry point for MTC (marker tray in CBCT), 3dPT (3d-printed tray), and PDG (pilot-drill guide) were 1.024 ± 0.446 mm, 1.027 ± 0.455 mm, and 1.009 ± 0.415 mm, respectively, and the mean total deviations at the implant apex were 1.026 ± 0.383 mm, 1.116 ± 0.530 mm, and 1.068 ± 0.384 mm. The angular deviation for the MTC group was 2.22 ± 1.54°. The 3dPT group revealed an angular deviation of 1.95 ± 1.35°, whereas the PDG group showed a mean angular deviation of 2.67 ± 1.58°. Although there were no significant differences among the three groups (P > 0.05), the navigation groups showed lesser angular deviations compared to the pilot-drill-guide (PDG) group. Implants in the 3D-printed tray navigation group showed higher deviations at both entry point and apex. Conclusions The accuracy of the evaluated navigation system was similar with the accuracy of a pilot-drill guide. Accuracy of both preoperative workflows (marker tray in CBCT or 3D-printed tray) was reliable for clinical use.